"Life if elsewhere": A diary study of female self-initiated expatriates' motivations to work abroad. Issue 3 (2nd August 2018) - Wechtler, Heidi
Abstract : Purpose: The purpose of this paper is to examine the motives of female childless self-initiated expatriates (SIEs) in deciding to work abroad, so far under-researched. Design/methodology/approach: The study departs from prior research in using a new methodological approach, i.e. the analysis of online diaries (blogs) to explore the motives of a specific population to relocate. Findings: The emergent model of motivations is based upon four main dimensions that emerged from the socially constructed experience of these single childless female SIEs: escape as main motivation, confrontation to reality, identity reconstruction and purpose of expatriation. Originality/value: The findings reveal new elements of motivations to move abroad such as the complete absence of the notion of career from the blog posts, replaced, however, by a feminist and existentialist reflection.